COVID and World Stock Markets: A Comprehensive Discussion - Jabeen, Shaista; Farhan, Muhammad; Zaka, Muhammad Ahmad; Fiaz, Muhammad; Farasat, Mobina (Frontiers in Psychology, 2022)
The COVID-19 outbreak has disturbed the victims' economic conditions and posed a significant threat to the worldwide economies and their respective financial markets (Baker, et al., 2020; Ramelli, & Wagner; 2020). The majority of the world stock markets have suffered in terms of trillion-dollar losses (Lyócsa, Baumöhl, Výrost, & Molná, 2020), and international financial institutions were forced to reduce their forecasted growth for 2020 and the years to come (Boone, Haugh, Pain, Salins, & Boone, 2020). The current research deals with the impact of the COVID-19 pandemic on the global stock markets. It has focused on the contingent effects of previous and current pandemics on the financial markets. It has also elaborated on the pandemic impact on diverse pillars of the economy. Irrespective of all these destructive effects of the pandemic, still hopes are there for the sharp rise and speedy improvements in global stock markets' performance.